Measurement of Temperature Dependence of Surface Tension of Alcohol Aqueous Solutions by Maximum Bubble Pressure Method - Naoki ONO; Takahiro KANEKO; Shotaro NISHIGUCHI; Masahiro SHOJI (Journal of Thermal Science and Technology, 2009)
The surface tension of some high-carbon alcohol aqueous solutions increases as the temperature rises above a certain temperature. There have been attempts to use such special solutions in thermal devices to promote heat transfer. In this study, the authors analyzed the temperature dependence of surface tension of these solutions to investigate this peculiar characteristic in detail. The test fluids were butanol and pentanol aqueous solutions as peculiar solutions, while pure water and ethanol aqueous solution were normal fluids. First, the authors adopted Wilhelmy's method to measure the surface tension during heating, but found that the influence of evaporation of the solution could not be completely eliminated. In this study, the maximum bubble pressure method was employed, which made it possible to isolate the measured solution from ambient air and eliminate the influence of evaporation of the solution. The authors succeeded in measuring the temperature dependence of surface tension, and obtained more reasonable data.